DIODE LASER IN PERIODONTAL TREATMENT (Tinjauan Pustaka) - Trijani Suwandi (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Latest technological advances have led to a constant desire to develop new approaches for the treatment of periodontal diseases, as a diode laser. Objective: This article reviews the diode laser is a soft tissue laser having a wavelength of 810 nm or 910-980nm, is being developed for a variety of uses in periodontal therapy. The diode lasers have been used in initial periodontal therapy for sulcular debridement, soft tissue surgery,  hypersensitive dentin, photodynamic therapy and also in implant treatment. Literatur review: The laser is a less-invasive method  compared with the conventional technique because it produces    little cell destruction. Diode lasers are used to overcome the disadvantages of conventional therapy, including postoperative pain dan discomfort, and suturing in conventional.  Conclusion: Laser use is beneficial as it requires minimal anaesthesia, lesser surgical time and good post-operative healing, reduced post operative pain and sensitivity, reduced patient anxiety.